Culture Shock and Multiculturalism Reclaiming a Useful Model from the Religious Realm. - Dutton, Edward (Newcastle upon Tyne : Cambridge Scholars Pub., 2012)
It used to be widely accepted amongst anthropologists that when they conducted fieldwork with foreign cultures they experienced something called 'culture shock.' This book will argue that 'culture shock' is a useful model for understanding an important part of human experience. However, in its most widely-known form, the stage model, 'culture shock' has been heavily influenced by the same anti-science, latter-day religiosity that has become so influential more broadly: Multiculturalism. This ...
TABLE OF CONTENTS; LIST OF ILLUSTRATIONS; COPYRIGHT ACKNOWLEDGEMENTS; ACKNOWLEDGEMENTS; CHAPTER ONE; CHAPTER TWO; CHAPTER THREE; CHAPTER FOUR; CHAPTER FIVE; CHAPTER SIX; CHAPTER SEVEN; CHAPTER EIGHT; CHAPTER NINE; CHAPTER TEN; CHAPTER ELEVEN; BIBLIOGRAPHY; INDEX OF NAMES.
Description based on print version record.
Keywords: Culture shock; Multiculturalism -- Religious aspects; Multiculturalism; Culture shock; Multiculturalism -- Religious aspects; POLITICAL SCIENCE / Globalization; Electronic books